2012
DOI: 10.1038/ncb2549
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting DNA damage response pathways by analysing protein localization and abundance changes during DNA replication stress

Abstract: Re-localization of proteins is a hallmark of the DNA damage response. We use high-throughput microscopic screening of the yeast GFP fusion collection to develop a systems-level view of protein re-organization following drug-induced DNA replication stress. Changes in protein localization and abundance reveal drug-specific patterns of functional enrichments. Classification of proteins by sub-cellular destination allows the identification of pathways that respond to replication stress. We analyzed pairwise combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
502
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 467 publications
(548 citation statements)
references
References 66 publications
(88 reference statements)
44
502
1
1
Order By: Relevance
“…A poor correlation was also observed between protein and mRNA fold changes in our dataset (SI Appendix, Fig. S23) and by Tkach et al (6), but a similar comparison of protein and mRNA levels during a diauxic shift showed better correlations between fold change and timing (16). Posttranscriptional mechanisms therefore seem to play a significant role in determining protein induction timing and abundance levels in response to MMS.…”
Section: Significancementioning
confidence: 59%
See 3 more Smart Citations
“…A poor correlation was also observed between protein and mRNA fold changes in our dataset (SI Appendix, Fig. S23) and by Tkach et al (6), but a similar comparison of protein and mRNA levels during a diauxic shift showed better correlations between fold change and timing (16). Posttranscriptional mechanisms therefore seem to play a significant role in determining protein induction timing and abundance levels in response to MMS.…”
Section: Significancementioning
confidence: 59%
“…These 16,731 movies consisted of 21 × 10 6 images, from which we analyzed a total of 1.5 × 10 8 cells, with an average of 199 cells quantified per image. By comparison, the original University of California, San Francisco (UCSF) yeast-GFP collection consisted of 14,562 images (5), the study by Tkach et al collected 74,664 images (6), and the entire University of Washington -Yeast Resource Center (UW-YRC) currently contains ∼1.2 × 10 6 images. Overall we performed the equivalent of more than 10,000 unique experiments.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In a high-throughput study, an Rmt2-green fluorescent protein fusion protein was shown to relocate to the nucleus after DNA damage in yeast cells induced by hydroxyurea or methyl methanesulfonate (88). These results suggest the possibility that Rmt2 has additional protein substrates in yeast, although it is also possible that methylation on the ribosomal protein is in some way coupled to DNA transcription or repair.…”
Section: An Unusual Protein Arginine Methyltransferase That Modifies mentioning
confidence: 85%